LARANGAN TAUKIL WAKIL WALI NIKAH DI KANTOR URUSAN AGAMA (KUA) KECAMATAN PANGENAN KABUPATEN CIREBON - Abdul Badri (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2017)
ABSTRACT                 Religion Affairs Office (KUA) subdistrict Pangenan, Cirebon regency has tasks and functions such as the service,  monitoring and record keeping marriage in their territory. Marriage which has force of law is that marriage which the prerequirement and  pillars of the marriage are met  and the marriage occurs in front of the marriage chief (The Official of Marriage Jotter/PPN). The pillars of marriage are:  The candidate of bride groom, The candidate of bride, Wali (The custodian), two witnesses and the consent (the agreement). In subdistrict Pangenan, the custodian in applying the consent his daughter or  his sister whom under his authority, represent his authority to marriage chief or PPN or the one who is intended to. The custodian represent  his authority to the one who is intended to (a representative) constitutes authority which is given by Islam freely. The consequence of the free authority occured that the custodian mandates it to a representative (wakil) and the representatative remandates to another one (in this research called taukil wakil wali nikah). Seeing this case, KUA subdistrict Pangenan prevents dan forbids the people to do so.The objective of the research is to reveal the people excuses in doing or applying taukil wakil wali nikah, to reveal the KUA excuses why they forbid the practice taukil wakil wali nikah and to know juridical position and implication of taukil wakil wali nikah.The research is a study case research with inductive analysis by applying  juridical and normative literature approach method, that is by studying in depth fiqih and ushul fiqih scribes and corpus, and rules and laws which are related to the case discussed. The source of  primer data which is gained and used is from library and personal literature collection. The data collection technique is by studying in depth the literature, documents, rules and laws and the experts’ opinions and thoughts. The collected data will be used as the thought basis theoritically, and then the data technique is written in logical and systematic essay.In the research conclusion reveals why the subdistrict Pangenan people’s excuses apply taukil wakil wali nikah are the disability factor in doing ijab (offer) and  the custom factor of the people always mandate the consent (the agreement) in a marriage. KUA subdistrict Pangenan excuse in preventing and forbidding taukil wakil wali nikah is because it is inappropriate for Standard Operating Procedure (SOP) in KUA, KUA is as the policy maker in the difference of opinion about  taukil wakil wali nikah and KHI, KMA and PMA do not regulate Taukil wakil wali  nikah. Taukil wakil wali nikah is not written explicitly in rules as the base of marriage in KUA and the juridical implication is that if the consent (the agreement/Ijab qobul) has not occured yet, the authority belongs to the real Wali (Muwakkil) and if the consent has occured, it is needed to repeat the consent (tajdîdu al-nikâh).